Mechanism of longitudinal bending fatigue failure of metal sandwich composite structures by laser welding - Jun YANG; Yuhao GUO; Xinyu XU; Gang LIU (Hanjie xuebao)
Laser-welded metal sandwich composite structures are increasingly used in the field of ships because of their excellent properties. However, compared with the traditional welding process, laser welding will introduce more complex welding defects between the panel and the web, which will seriously affect the fatigue properties of the structures. The four-point bending fatigue test was carried out with an I-type metal sandwich plate as the research object, and the test results were discussed by macroscopic analysis and scanning electron microscopy to obtain the crack initiation and propagation process. Based on the cohesive force model theory, numerical simulation was carried out to further reveal the crack propagation behavior of an I-type metal sandwich plate under fatigue load. The results show that the fatigue source region is located in the heat affected zone of laser welding, where the cracks first start and then spread along the web and the panel. Fatigue sources are generated in the laser welding area of multiple webs and lower panels of sandwich plates. However, due to the difference in initial defects in laser welding of different webs, the crack propagation speed is different. For the sample of I-type metal sandwich plate studied in this paper, the propagation area of different cracks presents a stepped form.